Measurement of CKM matrix elements in single top quark t-channel production in proton-proton collisions at vs=13 TeV - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer T. Thomas; Zhokin A. S. Aleksandr Sergeevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2020, 2020)
Title screen